Translating Korean Nature. Translation Strategies in Lithuanian and English Literary Translation - Tamošiūnienė, Lora (Research in Language, 2020)
World literatures today often impose a separation of narratives from their geographic and linguistic origins. Translated versions of literary texts that were created and received within local cultural contexts, when translated, enter new, foreign contexts. When translations into many other languages appear, a writer may expect many diverse valuations of one`s work. Literary texts in translation, in fact, are an inseparable from literary experiences for many readers and the study of translated texts has a long-standing tradition. The future of such texts may also lie in the emerging future reading - “distant reading” to quote Walkowitz` use of Moretti`s term. Among the strongest arguments in support of such reading is the possibility, through translated texts, to establish a more aesthetic distance towards the object of a fictional text in translation. Translation gives us as readers a new and different approach towards objects we fail to notice because of their familiarity. Nature scenes and objects may be included among such features of the narrative that could be more aesthetically appreciated in the translated versions. The paper compares translations of nature scenes and objects of Shin Kyung-Sook`s novel into English Please Look After Mom (2011) and into Lithuanian Prašau, pasirūpink mama (2019). The paper reveals the scope of translation strategies of domestication and foreignization through comparison of translation of nature scenes and items into Lithuanian and English.